Mechanisms of Phosphorus Acquisition and Lipid Class Remodeling under P Limitation in a Marine Microalga . Issue 4 (19th October 2017) - Mühlroth, Alice; Winge, Per; El Assimi, Aimen; Jouhet, Juliette; Maréchal, Eric; Hohmann-Marriott, Martin F.; Vadstein, Olav; Bones, Atle M.
Abstract : Corresponding lipidomic and transcriptomic data uncover the mechanism of P recycling and lipid class remodeling under P limitation in the alga Nannochloropsis oceanica. Abstract: Molecular mechanisms of phosphorus (P) limitation are of great interest for understanding algal production in aquatic ecosystems. Previous studies point to P limitation-induced changes in lipid composition. As, in microalgae, the molecular mechanisms of this specific P stress adaptation remain unresolved, we reveal a detailed phospholipid-recycling scheme in Nannochloropsis oceanica and describe important P acquisition genes based on highly corresponding transcriptome and lipidome data. Initial responses to P limitation showed increased expression of genes involved in P uptake and an expansion of the P substrate spectrum based on purple acid phosphatases. Increase in P trafficking displayed a rearrangement between compartments by supplying P to the chloroplast and carbon to the cytosol for lipid synthesis. We propose a novel phospholipid-recycling scheme for algae that leads to the rapid reduction of phospholipids and synthesis of the P-free lipid classes. P mobilization through membrane lipid degradation is mediated mainly by two glycerophosphoryldiester phosphodiesterases and three patatin-like phospholipases A on the transcriptome level. To compensate for low phospholipids in exponential growth, N. oceanica synthesized sulfoquinovosyldiacylglycerol and diacylglyceroltrimethylhomoserine. In this study, it was shown that an N. oceanica strain has a unique repertoire of genes that facilitate P acquisition and the degradation of phospholipids compared with other stramenopiles. The novel phospholipid-recycling scheme opens new avenues for metabolic engineering of lipid composition in algae.